Quasi uniformly accelered motion of quasi normal magnetic biharmonic particles in Heisenberg space with cold plasma - Körpınar, Zeliha; Körpınar, Talat (Sociedad Mexicana de Fisica, 2022)
In this paper, we firstly review the quasi uniformly accelerated motion (QUAM) with Fermi derivative by cold plasma in Heisenberg space. We define new quasi uniformly accelerated potential electric energy of quasi normal magnetic biharmonic particles and some Lorentz fields. Moreover, we design the new relationship between the quasi uniformly accelerated motion and the Fermi parallel transportation in cold plasma. Also, we collect new physical geometric designs for a quasi uniformly accelerated motion of normal magnetic biharmonic particles in Heisenberg space. Finally, we construct quasi uniformly accelerated potential electric energy with respect to its electric field and some quasi curvatures. © 2022. All Rights Reserved.
Keywords: Biharmonic particle; electrical energy; Heisenberg space; magnetic field; magnetic flux density; quasi plasma